Critical Discourse Analysis of Dua Garis Biru Novel (Novel Adaptation of Lucia Priandarini from Gina S. Noer's Scenario) - Putri, Meidiana; Mardikantoro, Hari Bakti; Baehaqie, Imam (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Language has a very important role in human life. As a tool for communication, language can be used in various ways, including through literary works in the form of novels. The purpose of this study is to identify and analyze the discourse of the characters in the novel "Dua Garis Biru" constructed by the author at the textual level (macrostructure, superstructure, and microstructure), social cognition, and social context. The approach used includes a methodological approach, namely descriptive qualitative, and a theoretical approach, namely Van Dijk's critical discourse analysis. The results of the study showed that the topic discussed was promiscuity by a pair of teenagers. The grooves used are mixed grooves. The parts of the text that are arranged as a whole form a scheme or plot from beginning to end in each chapter. The meaning to be conveyed by the author is displayed through the background, details, presuppositions, and intentions. The rhetorical elements of Van Dijk's discourse are graphics and metaphors. Social cognition consists of elements of knowledge and opinion or prejudice; presenting knowledge in each context of events according to knowledge in a particular field and the opinion or prejudice of the author is shown by conveying the author's opinion directly to the reader and providing an assessment of what is happening. The author gives an assessment of what is happening. Analysis of the social context of the novel "Dua Garis Biru" is related to the problem of school-age juvenile delinquency, women's reproductive health and the problem of female domination. Basically, this problem existed before the novel was published by the writer who saw this problem as a material conflict in it.